Organizational resilience and transformational leadership for managing complex school systems - Zadok, Ayala; Benoliel, Pascale; Schechter, Chen (Frontiers in Education, 2024)
Against the backdrop of global challenges facing schools, the present research analyzes the dynamics among transformational leadership, collective teacher efficacy, and organizational resilience in school systems, exploring whether leadership at the microsystem level can influence the resilience of broader ecosystems. This study explores the mediating role of collective teacher efficacy on the link between middleleaders' transformational leadership and organizational resilience. Two sources provided the data for this study: 103 middle-leaders and 506 randomly selected secondary school teachers. Structural equation modeling revealed that collective teacher efficacy fully mediates the relationship between middle-leaders' transformational leadership and organizational resilience. The findings of this study suggest that educational institutions can significantly increase their organizational resilience by enhancing transformational leadership and fostering a strong sense of collective teacher efficacy. Discussion encompasses theoretical and practical implications.